2020
DOI: 10.1029/2019ja027401
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Location of the Geotail Magnetopause Near Lunar Orbit: A Case Study

Abstract: The Earth's magnetopause is highly variable in location and shape and is modulated by solar wind conditions. On 8 March 2012, the ARTEMIS probes were located near the tail current sheet when an interplanetary shock arrived under northward interplanetary magnetic field conditions and recorded an abrupt tail compression at ∼(-60, 0, -5) R E in Geocentric Solar Ecliptic coordinate in the deep magnetotail. Approximately 10 minutes later, the probes crossed the magnetopause many times within an hour after the obliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
(106 reference statements)
1
8
0
Order By: Relevance
“…While thermal moonquakes are events caused by the day-night thermal expansion of rock at sunset, sunlight also tenuously electrifies and ionizes the Moon (Halekas et al, 2018), so a continuous magnetohydrodynamic and electrical interaction (of a weak electromagnetic field with trapped water molecules) could also be rupturing lunar rockinstead of or in combination with the thermal seismogenesis. The continuity of the interplay is supported further by a recent finding by Shang et al (2020) that the Earth's magnetotail does not constantly shield the Moon from external particles.…”
Section: Discussionmentioning
confidence: 66%
“…While thermal moonquakes are events caused by the day-night thermal expansion of rock at sunset, sunlight also tenuously electrifies and ionizes the Moon (Halekas et al, 2018), so a continuous magnetohydrodynamic and electrical interaction (of a weak electromagnetic field with trapped water molecules) could also be rupturing lunar rockinstead of or in combination with the thermal seismogenesis. The continuity of the interplay is supported further by a recent finding by Shang et al (2020) that the Earth's magnetotail does not constantly shield the Moon from external particles.…”
Section: Discussionmentioning
confidence: 66%
“…The CME was observed by the Wind spacecraft in the solar wind at the L 1 Lagrangian point and the magnetospheric response was detected by the pair of THEMIS-ARTEMIS satellites (P1 and P2) in lunar orbit. This event-from the Sun to Earth-is also well-studied in multiple articles (Liu et al, 2013;Patsourakos et al, 2016;Shang et al, 2020).…”
Section: Cme Observationsmentioning
confidence: 92%
“…A second small-scale set of simulations using a hybrid code (see Section 3) focuses on the response of the lunar wake when the magnetotail is first disturbed by the CME shock and plasma sheath. Shang et al (2020) reported independently on the effect of the disturbed geomagnetic tail at the Moon itself using THEMIS-ARTEMIS observations. As we discuss below, we reach very similar conclusions regarding the nature of the fast flows observed during the full Moon period.…”
mentioning
confidence: 99%
“…Similar events have also been reported in simulations (Haynes et al, 2015; Roytershteyn et al, 2015) and observations (Huang SY et al, 2017a, b). These structures, including recently reported kinetic‐scale flux ropes (Huang SY et al, 2016; Matsui et al, 2019; Sun WJ et al, 2019; Wang SM et al, 2019; Yao ST et al, 2020b) and kinetic‐scale magnetic dips and peaks (Hellinger and Štverák, 2018; Stawarz et al, 2018; Yao ST et al, 2018a; Hoilijoki et al, 2019), are new types of coherent structures found in turbulent plasmas, and play important roles in the cascade of turbulence from ion to electron scales (e.g., Huang J et al, 2019; Lucek et al, 2005; Karimabadi et al, 2014; Sahraoui et al, 2020; Shang WS et al, 2020). Yao ST et al (2019a) found that these KSMHs are coupled with electron cyclotron waves, electrostatic solitary waves, and whistler mode waves (Li Z et al, 2019).…”
Section: Introductionmentioning
confidence: 99%